Human and mouse TLR2 results in different activation of p38 and JNK signal pathway in HaCaT infected by Trichophyton rubrum and Microsporum canis - Su, Zhen; Deng, Weiwei; Zhan, Shuting; Li, Meirong; Yin, Songchao; Chen, Jian (Frontiers in Immunology, 2023)
It has long been recognized that inflammation to dermatophyte infection is different among various hosts, but the mechanism underlying is still not well understood. Toll-like receptor (TLR2), mediates the innate immune response against dermatophyte infection and is very important to trigger the inflammatory response to dermatophytes. Considering the different amino acid sequences and structures of TLR2, we speculated that TLR2 from different hosts will activate the downstream signal pathways to varying degrees, resulting in different inflammatory responses to dermatophytes. In this study, we constructed the mice-human fusion TLR2 expressed HaCaT (mhTLR2-HaCaT) by replacing the extracellular ligand recognition region of human TLR2 with that of the mouse. Compared with that of human TLR2 expressed HaCaT (hTLR2-HaCaT), p38 and JNK signal pathways were activated in mhTLR2-HaCaT after being infected by Trichophyton rubrum and Microsporum canis, respectively. Since p38 and JNK are the main pathways that transduce the signal for host recognition of dermatophytes and mediate the downstream inflammatory response, it suggested that the interspecific difference of TLR2 ectodomain may be one of the reasons for the different inflammatory manifestations between humans and mice infected by these two dermatophytes. Quite especially, the mouse-derived TLR2 extracellular recognition region is more effective in recognizing T. rubrum and M. canis to activate the downstream signal pathways, resulting in a tenser inflammatory response against these two dermatophytes.